Impact of haemodialysis on plasma carnitine concentrations in haemodialysis patients - Rehman, Sadia; Muhammad Farhan; Naveed, Asma; Mahmood, Shafaq; Muhammad Irfan Khattak (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the impact of haemodialysis on plasma carnitine levels. Method: The cross-sectional study was conducted from April 20, 2020 to May 10, 2022, at the dialysis unit of the nephrology ward of Jinnah Postgraduate Medical Centre, Karachi, and the Pakistan Navy Ship Shifa Hospital, Karachi, in collaboration with the Department of Biochemistry, University of Karachi, and comprised patients of either gender aged >18 years. They were divided into chronic kidney disease group A and end-stage renal disease group B. Control group C included subjects from the general population. Free carnitine and total carnitine values were detected using enzyme-linked immunosorbent assay. Acyl carnitine was estimated by applying the standard formula, and the ratio between acyl carnitine and free carnitine was calculated for accurate assessment of the carnitine status. Data was analysed using SPSS 23. Results: Of the 203 subjects, 143(70.44%) were cases and 60(29.55%) were controls. Among the cases, 120(84%) were recruited from Jinnah Postgraduate Medical Centre and 23(16%) from Pakistan Navy Ship Shifa Hospital. There were 60(29.55%) patients in group A, 83(40.88%) in group B and 60(29.55%) in group C. The mean age in group A was 47.90/5,65 years, it was 44.10/8.92 years in group B and 40.90/6.73 years in group C. There was a significant difference related to free carnitine, total carnitine, acyl carnitine values and the ratio between acyl carnitine and free carnitine values in groups A and B compared to control group C (p<0.05). Conclusions: Patients on maintenance haemodialysis developed were found to have developed carnitine deficiency. Key Words: Carnitine, Chronic kidney disease, Dialysis-related carnitine disorder, Haemodialysis.